(untitled) (Bangladesh Journal of Neuroscience, 2009)
This study was undertaken in the Department of Neurology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from January 2002 to December 2003. The objective of this study was to determine the initial neurologic symptoms of multiple sclerosis among Bangladeshi patients. A total of 25 respondents of multiple sclerosis patients as cases selected by McDonald et al. (2001) diagnostic criteria for multiple sclerosis were enlisted during the study period. The clinical details, investigations of the respondents were reviewed. Data were recorded in predesigned data collection sheet. Out of 25 cases, male patients were 12 (48%) and females were 13 (52%), ratio being 1:1.08. Majority of the patients presented at second, third and fourth decades of life. Most of the patients (56%) had acute onset, followed by subacute (28%) and insidious (16%). Certain clinical characteristics among Bangladeshi multiple sclerosis patients are noteworthy, namely, number of male and female patients almost equal (48% vs 52%), a higher rate of impaired vision (optic nerve involvement, 64%), motor weakness (92%), sphincteric disturbances (92%) and a lower rate of brainstem and cerebellar involvement. Painful tonic spasm was a prominent feature among Bangladeshi patients with multiple sclerosis (8 out of 25, 32%). Out of 25 patients, one (4%) expired due to aspiration pneumonia. Twenty four (96%) survived. Among them 9 (36%) has restricted activity, 7 (28%) were bedridden, 5 (20%) were chairbound, 2 (8%) had minor disability and were in work and 1 (4%) was completely normal. DOI: http://dx.doi.org/10.3329/bjn.v24i1.3035 Bangladesh Journal of Neuroscience 2008; Vol. 24 (1) :9-16